2012
DOI: 10.1371/journal.pone.0042690
|View full text |Cite
|
Sign up to set email alerts
|

The Guanine-Quadruplex Structure in the Human c-myc Gene's Promoter Is Converted into B-DNA Form by the Human Poly(ADP-Ribose)Polymerase-1

Abstract: The important regulatory role of the guanine-quadruplex (GQ) structure, present in the nuclease hypersensitive element (NHE) III1 region of the human c-myc (h c-myc) gene's promoter, in the regulation of the transcription of that gene has been documented. Here we present evidences, that the human nuclear poly(ADP-ribose)polymerase-1 (h PARP-1) protein participates in the regulation of the h c-myc gene expression through its interaction with this GQ structure, characterized by binding assays, fluorescence energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…This structure, which is in equilibrium with the double-stranded B-DNA form, prevents the binding of transcriptional activators [33]. Interestingly, it has been previously reported that PARP-1 binds to this sequence in vitro [34] and that this binding accelerates the in vitro conversion of the c-MYC GQ structure into its B-DNA form [35]. Our ChIP assays revealed that the enzyme also binds to an adjacent region, which contains that CT-I 2 element that has been previously recognized as biologically relevant for c-MYC transcription.…”
Section: Discussionmentioning
confidence: 98%
“…This structure, which is in equilibrium with the double-stranded B-DNA form, prevents the binding of transcriptional activators [33]. Interestingly, it has been previously reported that PARP-1 binds to this sequence in vitro [34] and that this binding accelerates the in vitro conversion of the c-MYC GQ structure into its B-DNA form [35]. Our ChIP assays revealed that the enzyme also binds to an adjacent region, which contains that CT-I 2 element that has been previously recognized as biologically relevant for c-MYC transcription.…”
Section: Discussionmentioning
confidence: 98%
“…Although there is a lot known about G4 structure formation and its impact on c-MYC transcription, only little is known about the 'disruption' of these G4 structures. So far, only three proteins, among them one helicase, have been described to support unfolding of G4 structures in c-MYC: CNBP, PARP-1, and Pif1 [99][100][101]. Nevertheless, a detailed analysis of these proteins and changes in G4-mediated c-MYC transcription are missing.…”
Section: Effects Of Helicases Acting On G4 Structures During Transcrimentioning
confidence: 99%
“…Both enzymes may, in addition, contribute to cancer progression, regulating the expression of critical genes. PARP-1 may stimulate transcription of the c-MYC gene, by converting the guanine-quadruplex structure in the human c-MYC gene's promoter into B-DNA, and thus facilitating access to this promoter for transcription factors [9] . OGG1, in turn, facilitates transcription of genes regulated by c-MYC.…”
Section: Introductionmentioning
confidence: 99%